L-band Brillouin-Erbium fiber laser pumped with 1480 nm pumping scheme in a linear cavity - Al-Mansoori, Mohammed Hayder; Naji, A. W.; Iqbal, S. J.; Abdullah, Mohammad Khazani; Mahdi, M. A. (IOP Publishing, 2007)
In this paper, a multiwavelength linear-cavity Brillouin-Erbium fiber laser pumped by a 1480 nm pump laser is demonstrated to operate in the L-band region. The issue of low gain efficiency of L-band in Erbium-doped fiber pumped with 980 nm pump lasers is resolved with this pumping scheme. The amount of 1480 nm pump power to produce the first Brillouin Stokes line oscillating in the cavity is 23.4 mW only. The proposed laser configuration has a wide tuning range of 16 nm from 1591 to 1607 nm with six Brillouin Stokes lines within this tuning range. The maximum number of 23 Brillouin Stokes lines with a spacing of 0.089 nm is achieved by setting the Brillouin pump wavelength at 1595.5 nm and its power is set at 3.2 mW.